2007
DOI: 10.1002/apj.82
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of processing seafood shells for eutrophication control

Abstract: Shells from the seafood processing industry in New Zealand are currently an under-utilized waste resource. In this study we investigate the processing conditions required for the creation of calcium oxide (lime) from green-lipped mussel (Perna canaliculus) and pacific oyster (Crassostrea gigas) shells. Lime is commonly used in wastewater treatment for the removal of phosphorous compounds from water, thus providing a means of eutrophication control. Mussel and oyster shells were processed in a horizontal tube f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…The moving bed biofilm reactor (MBBR) system, widely used in wastewater treatment process, was developed here based on the conventional activated sludge disposal and the fluidized-bed reactor (Currie et al, 2007). Its carriers can provide a suitable microenvironment for cell growth, leading to formation of a biofilm and a reduction in the washout from the system .…”
Section: Introductionmentioning
confidence: 99%
“…The moving bed biofilm reactor (MBBR) system, widely used in wastewater treatment process, was developed here based on the conventional activated sludge disposal and the fluidized-bed reactor (Currie et al, 2007). Its carriers can provide a suitable microenvironment for cell growth, leading to formation of a biofilm and a reduction in the washout from the system .…”
Section: Introductionmentioning
confidence: 99%
“…In a study carried out in New Zealand, Currie et al [3] showed that the use of calcined mussel shells eliminated around 90% of the phosphates in the water samples analysed, whereas the efficacy decreased to 40% when untreated mussel shells were used. However, information about the capacity of this material to retain heavy metals, specifically Hg(II), is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It is a highly effective biological treatment process that was developed on the basis of the conventional activated sludge process and the fluidizedbed reactor. [2,12] Researchers have shown that MBBR has many excellent traits such as high biomass, high Chemical Oxygen Demand (COD) loading, strong tolerance to loading impact, relatively smaller reactor size, *Correspondence to: Wen Ying Li, Key Laboratory of Coal Science and Technology, Taiyuan University of Technology, Taiyuan 030024, China. E-mail: ying@tyut.edu.cn no sludge bulking problem, etc.…”
Section: Introductionmentioning
confidence: 99%